INOVASI PENDAMPINGAN DIGITAL UNTUK MAHASISWA KKN: MENGATASI TANTANGAN GEOGRAFIS DENGAN MONITORING DAN EVALUASI ONLINE - Mustaqim Makki; Subairi; Ainur, Ainur Rofiq (Al Busyro : Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Community Service Program (KKN) in remote areas often faces geographical challenges, particularly in terms of monitoring and evaluation by supervising lecturers due to long distances. Emphasizing the need for direct involvement of lecturers, while physical access remains limited. Digital-based assistance through online platforms has become a crucial solution to overcome these obstacles. This study aims to develop and evaluate a digital mentoring model in KKN, using an action research methodology conducted in three cycles. Data were collected through student satisfaction surveys, digital activity logs, and in-depth interviews. The indicators measured include student participation, communication quality, and timely task completion. The results show that digital mentoring increases student engagement, with participation rising from 60% in the first cycle to 90% in the third cycle. Student satisfaction also increased from 45% to 85%, while timely task completion reached 95%. The use of digital platforms enables lecturers to provide faster and more effective feedback, although there are still challenges related to network infrastructure. Digital mentoring has proven effective in overcoming geographical challenges and improving the quality of student community service. This model can be more widely adopted in remote areas to support education and community service. This study recommends improving digital infrastructure and developing more accessible technology-based mentoring modules. Keywords: Online Mentoring, KKN Students, Geographical Challenges